Implementing a Physician Leader Compensation Program at a Major Community Hospital - Isser L. Dubinsky, Moshe Greengarten, Larry Grossman, Mark Hundert, Diane Sawatzky and Bill Whittaker (Law & Governance, 2008)
[This article was originally published in Healthcare Quarterly, Volume 11, Number 2.] The roles of physician leaders in Canadian hospitals and health regions are becoming more complex and time consuming. Physician leaders are increasingly being seen by hospital boards and executives as key to achieving strategic and operational outcomes. Given the growing importance of these roles and the increasing performance expectations being placed on physician leaders, it is critical that organizations are able to recruit and retain individuals who demonstrate the skills required to fulfill these critical roles or commit themselves to acquiring them.
Keywords: Physician compensation, physician leaders, recruitment and retention, health human resources